2024
DOI: 10.1021/acsnano.3c12638
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism behind the Controlled Generation of Liquid Metal Nanoparticles by Mechanical Agitation

Nur-Adania Nor-Azman,
Mohammad B. Ghasemian,
Richard Fuchs
et al.

Abstract: The size-controlled synthesis of liquid metal nanoparticles is necessary in a variety of applications. Sonication is a common method for breaking down bulk liquid metals into small particles, yet the influence of critical factors such as liquid metal composition has remained elusive. Our study employs high-speed imaging to unravel the mechanism of liquid metal particle formation during mechanical agitation. Gallium-based liquid metals, with and without secondary metals of bismuth, indium, and tin, are analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In recent, direct observation of the emulsification behavior of molten Ga and Ga–based alloy during sonication in water by using a high-speed camera [11] , [12] , [13] . Their study revealed a relationship between the emulsification of molten Ga and cavitation diameter.…”
Section: Introductionmentioning
confidence: 99%
“…In recent, direct observation of the emulsification behavior of molten Ga and Ga–based alloy during sonication in water by using a high-speed camera [11] , [12] , [13] . Their study revealed a relationship between the emulsification of molten Ga and cavitation diameter.…”
Section: Introductionmentioning
confidence: 99%